Art is life : icons and iconoclasts, visionaries and vigilantes, and flashes of hope in the night - Saltz, Jerry, 1951- (Riverhead Books, 2022)
"Jerry Saltz is one of our most-watched writers about art and artists, and a passionate champion of the importance of art in our shared cultural life. Since the 1990s he has been an indispensable cultural voice: witty and provocative, he has attracted contemporary readers to fine art as few critics have. An early champion of forgotten and overlooked women artists, he has also celebrated the pioneering work of African American, LGBTQ+, and other long-marginalized creators. Sotheby's Institute of Art has called him, simply, "the art critic." Now, in Art Is Life, Jerry Saltz draws on two decades of work to offer a real-time survey of contemporary art as a barometer of our times. Chronicling a period punctuated by dramatic turning points-from the cultural reset of 9/11 to the rolling social crises of today-Saltz traces how visionary artists have both documented and challenged the culture. Art Is Life offers Saltz's eye-opening appraisals of trailblazers like Kara Walker, David Wojnarowicz, Hilma af Klint, and Jasper Johns; provocateurs like Jeff Koons, Richard Prince, and Marina Abramović; and visionaries like Jackson Pollock, Bill Traylor, and Willem de Kooning. Saltz celebrates landmarks like the Obama portraits by Kehinde Wiley and Amy Sherald, writes searchingly about disturbing moments such as the Ankara gallery assassination, and offers surprising takes on figures from Thomas Kinkade to Kim Kardashian. And he shares stories of his own haunted childhood, his time as a "failed artist," and his epiphanies upon beholding work by Botticelli, Delacroix, and the cave painters of Niaux. With his signature blend of candor and conviction, Jerry Saltz argues in Art Is Life for the importance of the fearless artist-reminding us that art is a kind of channeled voice of human experience, a necessary window onto our times. The result is an openhearted and irresistibly readable appraisal by one of our most important cultural observers"--